Empowerment Poor Communities with the Strengths - Perspective in Empowerment Theory - Ardent Kloee Titu Eki; Christina Ngadilah; Yansestina Erlince Eky (Green Publisher Indonesia, 2024)
Empowerment is one of strategies to alleviate poverty .Poverty is something that does not stand alone, but is formed from various aspects concerning humans, especially economic, social, environmental which will affect their lives. This paper will discuss the importance of strengths-perspective as a new paradigm in social work in the empowerment program to achieve the expected goals of solving the problem of poverty. This paper will use literature studies such as books, articles, and other sources relevant to the topics discussed. This study show that the principle of strengths-perspective is very much needed in an empowerment program. Strength based approaches not to replace another theory that has been used for a long time,in compiling and analyzing, social policy or programs empowerment of poor communities.